2014
DOI: 10.1242/dev.106005
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear removal during terminal lens fiber cell differentiation requires CDK1 activity: appropriating mitosis-related nuclear disassembly

Abstract: Lens epithelial cells and early lens fiber cells contain the typical complement of intracellular organelles. However, as lens fiber cells mature they must destroy their organelles, including nuclei, in a process that has remained enigmatic for over a century, but which is crucial for the formation of the organelle-free zone in the center of the lens that assures clarity and function to transmit light. Nuclear degradation in lens fiber cells requires the nuclease DNase IIβ (DLAD) but the mechanism by which DLAD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 47 publications
4
56
2
Order By: Relevance
“…We found that Cdk1 is nuclear and cytoplasmic in the bow region, but gradually becomes more nuclear toward the presumptive organelle free zone toward the center of the lens (Fig. 2A)(Chaffee et al, 2014). Cdk1 becomes activated through dephosphorylation by members of the Cdc25 phosphatase proteins.…”
Section: Relationship Between Mitosis and Lfcdmentioning
confidence: 91%
“…We found that Cdk1 is nuclear and cytoplasmic in the bow region, but gradually becomes more nuclear toward the presumptive organelle free zone toward the center of the lens (Fig. 2A)(Chaffee et al, 2014). Cdk1 becomes activated through dephosphorylation by members of the Cdc25 phosphatase proteins.…”
Section: Relationship Between Mitosis and Lfcdmentioning
confidence: 91%
“…The reduction in phosphorylated LC3b proteins supports this possibility. In addition, lamin B phosphorylation mediated by Cdk1, a process that occurs during normal mitosis, is required for denucleation (Caceres et al, 2010;Chaffee et al, 2014). Further experiments are required to probe signaling upstream of JNK/mTOR, the phosphorylation of lamin B by Cdk1, and yet to be identified steps in the cascade of cellular and molecular events leading to nuclear degradation in lens fibers (Morishita and Mizushima, 2016).…”
Section: Kip2mentioning
confidence: 99%
“…Between E16 and E18, central lens fiber cells initiate the removal of cell nuclei, a process that requires the nuclease DnaseIIβ (Bassnett, 1997, 2009; Chaffee et al, 2014; Nakahara et al, 2007). Both Fgfr2 Δ/Δ and (Pten/R2) Δ/Δ lenses retained nuclei in central lens fiber cells (Fig.…”
Section: Resultsmentioning
confidence: 99%